Terminalia chebula (Harar) Characterization by using Morphological Descriptors in Himalayan Region - Guleria, Vipan; Chaudhary, Punit; Vashisth, Amol; Sharma, Kamal; Selvan, Thiru; Thakur, Sanjeev (Indian Forester, 2021)
Terminalia chebula Retz. plays a crucial role in foodstuff, medicine, industry, and environmental protection. The skill of recognizing the variants of the species is very important in some applications, including conservation, strain types identification and performance of strains under different agro-ecological situation. However, it is a difficult task to identify plant species because it requires specialized knowledge. Developing morphological classification system for different genotypes and variants is necessary and valuable since it can help specialists as well as the public to identify and avoid cheating. It is a medicinal tree species which is highly valued in Indian system of medicine viz Ayurveda, Yunani, Sidha etc. Terminalia chebula trees are naturally distributed in the Sub Himalayan tract up to 1400 m above mean sea level in subtropical region, although planted trees can be seen in throughout the Northern Indian region. Research has been conducted to survey, locate the variations, identify the productive strains and also identify the ecological distribution of T. chebula in different agro-ecological regions of Himalayan region. The results indicated a high diversity in fruit and leaf shapes. Nine shapes of fruits were observed in the studied locations (Oblong â€œMatka typeâ€, Oblong dark colour with short neck, Pyriform, Pyriform type fruit with Medium neck, Narrowly obovate without neck, Clavate with prominent neck, Oval, Ellipsoid and light coloured and Narrowly obovate medium in size with acute tip. Analysis showed that there were significant differences in leaf morphmetric characters, too. Nine shapes of leaves were observed in the region viz. Cuspidate, Elliptic, Aristate, Obtuse, Lanceolate, Ovate, Oblique, Ovoid and Oblong.